Are Active Teaching Methods Suitable for All Generation Y Students? - Creativity as a Needed Ingredient and the Role of Learning Style - Nina Pološki Vokić; Ana Aleksić (MDPI AG, 2020)
Active teaching methods are emphasized as an important part of an effective teaching process for Generation Y students. Still, some individual characteristics, such as creativity and learning style, need to be considered as they can affect outcomes of the learning process. Empirical research on the students’ preferences for various active and passive teaching methods was done on a sample of graduate students from the Faculty of Economics and Business in Zagreb. Perceptions of students regarding 52 individual teaching methods, and teaching methods bundles were investigated. Findings reveal that more creative students, as well as activists and pragmatists, and especially reflectors while learning, do exhibit the greater inclination towards active teaching methods.